The local environment of Dy3+in selenium-rich chalcogenide glasses - Barney, Emma R.; Tang, Zhuoqi; Seddon, Angela; Furniss, David; Sujecki, S.; Benson, Trevor M.; Neate, Nigel; Gianolio, Diego (Royal Society of Chemistry, 2014)
The environment of Dy3+ is investigated when it is added as DyCl3 or Dy foil into two base glasses, Ge16.5As19−xGaxSe64.5, where x = 3 or 10 at%, at doping levels between 0 and 3000 parts per million by weight (ppmw) Dy3+. Extended X-ray Absorption Fine Structure demonstrates the glasses doped with Dy foil, or less than 1000 ppmw Dy3+ as DyCl3, contain Dy ions that are fully incorporated into the glass network and are coordinated by 7–8 Se atoms. However, when the DyCl3 dopant is present in concentrations ≥1000 ppmw Dy3+ the environment is dominated by Dy–Cl bonds. Furthermore, these Dy–Cl environments are nanocrystalline, retaining chemical order beyond the first coordination shell. By comparison with XRD and FTIR results, we report that the presence of α-Ga2Se3 crystallites in the glass, and the increased optical scattering in the fibres, are both related to the presence of DyCl3 crystallites.